The Position of Private Lecturers in Hinger Education in the Perpective of Labor Law - Yeltriana; Ismed Batubara; Al Kausar (P3M IAI Nusantara Batang Hari, 2023)
The working relationship is an industrial relations are subject to labor laws. Permanent Lecturer status remains the same as permanent workers based on Time Indefinite (PKWTT). While Lecturer do not remain the same as contract workers based on Specific Time Work Agreement (PKWT). Law No. 14 of 2005 on Teachers and Lecturers do not regulate in detail the rights and obligations of faculty and private universities, particularly in the context of social welfare and lecturer. But PTS is obliged to provide welfare and social security, especially for tenured faculty. Disputes between faculty with PTS is that the settlement of industrial disputes based on law No. 2 of 2004 on Industrial Relations Dispute Settlement.